Study on the Influence of Tooth Surface Friction on Bifurcation Characteristic of Multiple Clearance Bending and Torsion Coupling Gear - Liu Zhiyu Liu Bo Dong Hao (Jixie chuandong)
In order to study the gear bifurcation characteristic under the influence of tooth surface friction, based on the lumped parameter theory, considering the non-linear factors such as tooth surface friction, time-varying meshing stiffness, gear backlash and bearing clearance, a six-degree-of-freedom bending-torsion coupled vibration model of gear pairs is established. The Runge-Kutta numerical method is used to solve the model, and the influence of tooth surface friction on the bifurcation characteristics of the system is analyzed with various parameters. The results show that with the increase of rotational speed, the chaotic characteristics of the toothless surface friction are obvious, and with the increase of friction coefficient, the bifurcation outside the chaotic region will lead to the bifurcation inside the chaotic region. With the increase of tooth clearance, the amplitude of the system increases continuously without the tooth surface friction, and the chaotic state is inhibited with the increase of the tooth surface friction. With the increase of tooth surface friction, the blocking trend and suppression effect of the chaotic region are more significant with the increase of the damping coefficient.